Heart disease mortality in the Philippines from 1960 to 2019: a big data analysis - Kathleen Laum Cabanlit; Ralf Benjo Goder Morilla; Angel Mae Frias Luga; Jamerah Baniaga Sidic; Chin-chin Jimenea Demayo; Cesar Guinanao Demayo (Intelektual Pustaka Media Utama, 2023)
Heart diseases remain one of the major health concerns worldwide, inflicting a tremendous financial burden, especially in low to middle-income countries like the Philippines. An exhaustive time-trend analysis, including recent data, is essential to measure the nation's progress in cardiac health, capturing the effect of national-scale changes over time. Thus, using stored data from the Philippine health statistics, this study analyzed trends and profiles of heart disease mortality in the Philippines from 1960 to 2019 and discussed relevant national policies for greater recognition and awareness. Ischaemic heart disease constituted the most significant proportion of mortality among all types. Steadily increasing trends by cause, gender, age group were observed, and with males and the elderly population having higher rates. Regional differences also existed, having the highest rates in Luzon, the Visayas, and Mindanao respectively. Like global patterns, heart disease remained one of the country's leading causes of mortality over decades. Differences between genderes, age groups, and regions are attributed to complex and interrelated factors making males, the elderly, and highly urbanized areas most vulnerable among the population.